Seamless integration of heterogeneous devices and access control in smart homes and its evaluation. (2nd January 2017) - Kim, Ji Eun; Barth, Tassilo; Boulos, George; Yackovich, John; Beckel, Christian; Mosse, Daniel
ABSTRACT: The recent trend of ubiquitous access to embedded physical devices over the Internet as well as increasing penetration of wireless protocols such as ZigBee has raised attention to smart homes. These systems consist of sensors, devices and smart appliances that can be monitored and controlled remotely by human users and cloud services. However, the lack of a de facto communication standard for smart homes creates a barrier against the interoperability of devices from different vendors. We address this challenge by proposing a holistic and extensible software architecture that seamlessly integrates heterogeneous protocol- and vendor-specific devices and services, while making these services securely available over the Internet. Our architecture is developed on top of the Open Services Gateway initiative framework and incorporates a semantic model of a smart home system. As a result, we come closer to semantic interoperability – the ability to integrate new applications and drivers into the deployed system during runtime. Furthermore, we integrate a new access control model for specific smart home scenarios. As a proof of our concept, we demonstrate the seamless semantic discovery of home devices at runtime by integrating several protocols including X10, Insteon, ZigBee and Universal Plug-and-Play into a real test. Using smart phones and cloud services together with our home gateway implementation, we further demonstrate the ease of integration of new applications and drivers. We show the scalability of our solution by evaluating the execution time for different numbers of devices and configurations of the semantic device discovery.